2003
DOI: 10.1203/01.pdr.0000086904.52847.2a
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Endothelial Nitric Oxide Synthase (eNOS) in the Rat Liver

Abstract: Transition from fetal to postnatal life requires significant changes in cardiac, pulmonary, and hepatic blood flow. As such, there must be changes in vascular control in these vascular systems. Vascular resistance, a major contributor to blood flow, is mediated in the ductus arteriosus and pulmonary vasculature by endothelial nitric oxide synthase (eNOS). This study was conducted to determine the ontogeny of hepatic eNOS expression and activity. Additionally, the expression and activity of inducible nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…Obolenskaya et al [14] used methods similar to those reported here and demonstrated that NO production is very low in adult rats. In addition, NOS 3 (eNOS) protein in the liver reaches a maximum 20 days after birth, and these levels persist in adults [13]. These reports were in good agreement with the present study, where minimal NO production was observed in the livers of normal 5-week-old rats, when NOS 3 protein expression is almost at the same level as in adults.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Obolenskaya et al [14] used methods similar to those reported here and demonstrated that NO production is very low in adult rats. In addition, NOS 3 (eNOS) protein in the liver reaches a maximum 20 days after birth, and these levels persist in adults [13]. These reports were in good agreement with the present study, where minimal NO production was observed in the livers of normal 5-week-old rats, when NOS 3 protein expression is almost at the same level as in adults.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, NOS 1 and NOS 2 mRNA were not detected in the liver during juvenile stages. Previous report has suggested that NOS 3 is the only NOS isoform expressed in the liver of newborn rats, and its expression continues into adulthood [13]. Thus, it is suggested that the NO production in the liver was derived from NOS 3.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This cannot be supported by our findings of eNOS expression in lung tissue. The developmental pattern of eNOS expression is thought to be such that it peaks after the neonatal period as shown in porcine lung (2) and also rat liver (28). In the present study, we documented that eNOS expression in rat lung was similar across ages with a tendency toward higher values in the fetus and newborn compared with adult lung.…”
Section: Discussionsupporting
confidence: 72%
“…At least two isoforms of NOS are found in the liver: endothelial NOS (eNOS) and inducible NOS (iNOS). NO generated by eNOS plays a vital physiological role in maintaining appropriate microvascular tone and blood flow and exhibits protective effects (30). Studies have shown that nonspecific NOS inhibition or genetic deletion of eNOS results in reduced microvascular perfusion and aggravated liver injury (10,17).…”
mentioning
confidence: 99%